THE COMPUTER SUPPORT OF FUTURE NAVIGATORS' OF "SEAWORTHY ASTRONOMY". - I.V. Sokol (Kherson State University, 2010)
In the given article the questions of computer support during the teaching of navigators on subject discipline "Seaworthy Astronomy" are considered at definition of calculated altitude and a luminary azimuth.